Paying out-of-pocket for drugs, diagnostics and medical services : a study of households in three Indian States - Alam, Moneer (India Studies in Business and Economics, 2013)
In India there is a high incidence of morbidity and malnutrition coupled with low standards of public health and expensive medical care. Despite several policy initiatives and many attempts to promote a healthy society, health remains an issue of concern. Policy-makers recognise that the country suffers unacceptably high levels of disease and premature death. A 2005 report from the National Commission on Macroeconomics and Health (NCMH) claims that private out-of-pocket (OOP) health expenditure often has a catastrophic effect on the consumption of basic goods and services for low-income households, forcing many below the poverty line and often blocking private intergenerational flows, severely affecting family members including the co-residing elderly, especially women. As poverty, malnutrition and enormous disparities are widespread, particularly in rural areas and urban slums, reliance on private health providers is fraught with serious economic consequences. Disease prevalence among these groups is particularly high. The market plays an increasingly important role in delivering health and diagnostic services. Infrastructural bottlenecks faced by central, state and local government health services force public health service users to access private medical care and incur very high out-of-pocket (OOP) expenses. All these issues are in direct contradiction to India's National Population Policy (2000) and National Health Policy (2002).   This book highlights some of these neglected issues, and focuses largely on private expenditure on drugs and medicines for the treatment of ailments both with and without hospitalisation. It examines private OOP health expenditures in rural and urban households after breaking them down into the various healthcare service components including drugs and medicines (which constitute about 75 to 80 percent of OOP health expenditure), and assesses the extent of capital sample households borrow to finance medical expenditure and the effect on their basic food and non-food consumption requirements.